2021
DOI: 10.48550/arxiv.2107.04066
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Flows, growth rates, and the veering polynomial

Abstract: For certain pseudo-Anosov flows ϕ on closed 3-manifolds, unpublished work of Agol-Guéritaud produces a veering triangulation τ on the manifold M obtained by deleting ϕ's singular orbits. We show that τ can be realized in M so that its 2-skeleton is positively transverse to ϕ, and that the combinatorially defined flow graph Φ embedded in M uniformly codes ϕ's orbits in a precise sense. Together with these facts we use a modified version of the veering polynomial, previously introduced by the authors, to compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…It quickly became evident that veering triangulations exist also on non-fibered 3-manifolds [12,Section 4]. In unpublished work Agol and Guéritaud showed that a veering triangulation can be constructed from a pair (Ψ, Λ), where Ψ is a pseudo-Anosov flow on a closed 3-manifold, and Λ is a finite, nonempty collection of closed orbits of Ψ containing all singular orbits of Ψ and such that Ψ does not have perfect fits relative to Λ; see [14,Section 4]. The original fibered setup discussed in [1] is just a special case in which Ψ is the suspension flow of a pseudo-Anosov homeomorphism, and Λ consists only of the sigular orbits of Ψ.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It quickly became evident that veering triangulations exist also on non-fibered 3-manifolds [12,Section 4]. In unpublished work Agol and Guéritaud showed that a veering triangulation can be constructed from a pair (Ψ, Λ), where Ψ is a pseudo-Anosov flow on a closed 3-manifold, and Λ is a finite, nonempty collection of closed orbits of Ψ containing all singular orbits of Ψ and such that Ψ does not have perfect fits relative to Λ; see [14,Section 4]. The original fibered setup discussed in [1] is just a special case in which Ψ is the suspension flow of a pseudo-Anosov homeomorphism, and Λ consists only of the sigular orbits of Ψ.…”
Section: Introductionmentioning
confidence: 99%
“…The connection between veering triangulations and pseudo-Anosov flows has been explored further by Agol-Tsang [2], Landry-Minsky-Taylor [14], and Schleimer-Segerman [20,21]. From their work it follows that veering triangulations can be viewed as combinatorial tools to study pseudo-Anosov flows.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation